Reading Alice Munro with Jacques Lacan - Murray, Jennifer, 1963- (McGill-Queen's University Press, 2016)
"This work examines Alice Munro's writing from the perspective of Lacanian psychoanalytic theory. The project is based on the recognition that Munro's talent lies largely in her intuitive grasp of the complexities of human subjectivity, and in her ability to make those subtleties and ambiguities perceptible. The Lacanian approach to the analysis of the human psyche allows the reader not only to perceive those human complexities, but to understand what underpins them. In its attention to the place of language in the formation of the subject, Lacanian theory provides the necessary framework for a close textual reading that targets the libidinal structuring of the text. (The Lacanian concept of jouissance involves enjoyment, orgasm, but also a compulsion to transgress and go beyond the pleasure principle, thereby bringing inevitable pain.) Each Munro story chosen for analysis deals with particular aspects of the desires and enigmas of feminine subjectivity. This involves a progression that corresponds, logically speaking, to internal conflicts or questionings appropriate to different moments in life. The book begins by looking at stories in which the main character is a child, confronted by the inscrutability of parental injunctions, desires, and symbolic functions. Part II offers analyses of stories that deal with adult perspectives, notably in the field of love relationships, where desire, jouissance and love are examined in a serious effort to follow the logic of the texts to their point of impossibility : there where meaning stops. The final section draws certain conclusions from the analyses and extends their implications to other works by Munro, seeing in the writing the trace of the particular 'fixion' (a combination of fiction and fixation) of Munro's textual narratives."--